URGENSI MODERNISASI HUKUM RUANG ANGKASA TENTANG AKTIVITAS EKSPLORASI DAN EKSPLOITASI SUMBER DAYA DI BULAN SEBAGAI PENGEMBANGAN DARI THE MOON AGREEMENT 1979 - Akmal Hidayat; Maria Maya Lestari; Ledy Diana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
ABSTRACT The development of national space law has surpassed international space law. International space law needs to be developed because the exploitation of natural resources from the moon and other celestial bodies is closer than ever to becoming a reality. There is an urgency to develop existing international law or create new regulations that can accommodate resource mining activities in space. So the purpose of writing this thesis are: First, to know the urgency of modernize space law regarding resource exploration and exploitation activities on the moon. Second, find a solution to fill the legal gaps regarding the use of resources on the moon. This research is normative legal research, namely legal research carried out by examining library materials with secondary data. Then, the data that has been collected will be processed and analyzed using descriptive methods by sorting the data so that a conclusion can be drawn. From the results of the research problem there are two main things that can be concluded. First, there is an urgency to develop international regulations regarding the use of resources in space, especially on the moon because it has not been specifically discussed in the 1967 Space Treaty and the 1979 Moon Agreement. Second, solutions that can be taken to fill legal gaps regarding the use of resources in outer space, especially on the moon, are by using analogies with the law of the sea in developing space law, improving the international space legal framework, and developing institutions tasked with supervising exploitation activities. resources and space mining. Keywords: Space, Moon, Resources, Exploitation, Mining